2010
DOI: 10.1001/archinternmed.2010.382
|View full text |Cite
|
Sign up to set email alerts
|

Marked Variability of Monacolin Levels in Commercial Red Yeast Rice Products

Abstract: We found striking variability in monacolin content in 12 proprietary RYR products and the presence of citrinin in one-third of the formulations tested. Although RYR may have potential as an alternative lipid-lowering agent, our findings suggest the need for improved standardization of RYR products and product labeling. Until this occurs, physicians should be cautious in recommending RYR to their patients for the treatment of hyperlipidemia and primary and secondary prevention of cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(109 citation statements)
references
References 36 publications
4
97
0
4
Order By: Relevance
“…Further research indicated that the substance had received some public attention including from regulatory agencies in France and America (ANSES, 2014;FDA, 2007) based on concerns regarding the concentration of the active ingredient (Gordon, 2010), and concerns reported in the press regarding its contamination with citrinin (Harding, 2008). Alongside this, there were also reports in the popular press (Macrae, 2008) citing research (Lu et al, 2008) on its positive impact, and medical advisory sites providing a science-literacy perspective on this (NHS Choices, 2008).…”
Section: Self-report Information Seeking and Information Seeking Taskmentioning
confidence: 99%
“…Further research indicated that the substance had received some public attention including from regulatory agencies in France and America (ANSES, 2014;FDA, 2007) based on concerns regarding the concentration of the active ingredient (Gordon, 2010), and concerns reported in the press regarding its contamination with citrinin (Harding, 2008). Alongside this, there were also reports in the popular press (Macrae, 2008) citing research (Lu et al, 2008) on its positive impact, and medical advisory sites providing a science-literacy perspective on this (NHS Choices, 2008).…”
Section: Self-report Information Seeking and Information Seeking Taskmentioning
confidence: 99%
“…The level of citrinin in red yeast rice at a commercial rate varies greatly, ranging from non-detected by using HPLC (Liu and Xu, 2013) to 189 ppm (Gordon et al, 2010). Such variations are influenced by Monascus strains, fermentation substrate, and the environment.…”
Section: Citrininmentioning
confidence: 99%
“…The possible decrease in carotenoid and fat-soluble vitamin levels by sterols/stanols can be prevented with a balanced diet rich in these nutrients. 185 Based on LDL-C lowering and the absence of ad- 145 but the long-term safety of the regular consumption of these products is not fully documented. However, side effects similar to those observed with statins have been reported in some people using these nutraceuticals.…”
Section: Phytosterolsmentioning
confidence: 99%